Efficient taxation of fuel and road use - Geir H. M. Bjertnæs (Statistics Norway, Research Department, 2019)
This study calculates efficient taxes on fuel and road use designed to combat driving related externalities. The study shows that the efficient road user charge on fuel is below the marginal mileage-related damage to prevent tax avoidance due to an excessive economic driving-style. The current US tax rate on gasoline is way below the efficient tax rate while the current UK rate is slightly above the efficient rate in this case. The efficient tax on fuels exceeds the marginal damage of CO2-emissions to promote an economic driving-style when the tax is combined with a GPS-based tax on road use. The efficient GPS-based tax rate on road use is reduced below the marginal damage of mileage-related externalities in this case.
Keywords: H2; H21; H23; Q58; R48; 330; Transportation; optimal taxation; environmental taxation; global warming